Exploring seagrass perceptions in the Maldives: insights from a nationally distributed social media survey - Jessica Arnull; Aishath Mufliha Ziyadh; Aminath Shaha Hashim; Alexander W. Tudhope; A. Meriwether W. Wilson (Ocean & Coastal Management, 2026)

Experimental nutrient enrichment during thermal stress reduces bleaching severity in an oligotrophic reef setting, Maldives - Jessica Arnull; Aminath Shaha Hashim; Raja S. Ganeshram; A. Meriwether W. Wilson; Hassan Moosa; David S. Reay; Aishath Mufliha Ziyadh; Alexander W. Tudhope (Marine Pollution Bulletin, 2026)

Seagrass regulates elevated water column nutrients to promote leaf growth in a coral reef setting, Maldives - Jessica Arnull; Aminath Shaha Hashim; Aishath Mufliha Ziyadh; Amber L. Carter; Hassan Moosa; A. Meriwether W. Wilson; Raja S. Ganeshram; Alexander W. Tudhope (Marine Environmental Research, 2025)

Seagrass is an early responder to nitrogen enrichment in oligotrophic oceanic coral atoll environments - Jessica Arnull; Aminath Shaha Hashim; Raja S. Ganeshram; Hassan Moosa; A. Meriwether W. Wilson; Alexander W. Tudhope (Marine Pollution Bulletin, 2024)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.